Microbial oxidation of nitrogen supplied as selected organic nitrogen compounds in the South Atlantic Bight. (10th December 2018) - Damashek, Julian; Tolar, Bradley B.; Liu, Qian; Okotie‐Oyekan, Aimee O.; Wallsgrove, Natalie J.; Popp, Brian N.; Hollibaugh, James T.
Abstract: Dissolved organic nitrogen (DON) can account for a large fraction of the dissolved nitrogen (N) pool in the ocean, but the cycling of marine DON is poorly understood. Recent discoveries that urea‐ and cyanate‐N can be oxidized by some strains of Thaumarchaeota suggest that these abundant microbes may be able to access and oxidize a fraction of the DON pool. However, measurements of the oxidation of N supplied as DON compounds are scarce. Here, we compare oxidation rates of N supplied as a variety of DON compounds in samples from Georgia coastal waters, where nitrifier communities are numerically dominated by Thaumarchaeota. Our data indicate that polyamine‐N is particularly amenable to oxidation compared to the other DON compounds tested. Oxidation of N supplied as putrescine (1, 4‐diaminobutane) was generally higher than that of N supplied as glutamate, arginine, or urea, and was consistently 5–10% of the ammonia oxidation rate. Our data also suggest that the oxidation rate of polyamine‐N may increase as the length of the carbon skeleton increases. Oxidation of N supplied as putrescine, urea, and glutamate were all highest near the coast and lower further offshore, consistent with patterns of ammonia oxidation in these waters. Though it is unclear whether oxidation of polyamine‐N reflects direct oxidation by Thaumarchaeota or combines remineralization and subsequent ammonia oxidation, more rapid oxidation of N from putrescine compared to amino acids or urea suggests that polyamine‐N may contribute significantly to nitrification in the ocean.